Implementation of VRRP for Internet Optimization at Class I Sultan Iskandar Muda Meteorological Station - Banda Aceh - Kasihan Muhammad Fajar; Wahyu Fuadi; Yesy Afrillia (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
Class I Sultan Iskandar Muda - Banda The Aceh Meteorological Observatory is an environmental engineering implementing agency for observation and data processing, under the responsibility of the Meteorology, Climatology and Geophysical Agency. When using a government agency`s Internet network, failures such as unstable connections, failures, errors, and broken main routers often occur. If the main router goes down, no backup is available. To avoid this, a backup router must exist. Therefore, in this study, we apply an implementation of the virtual redundant router protocol to optimize the Internet network. The reseacrh aims explore to investigate the quality of WiFi network services. Researchers use her QoS analysis using packet loss, delay, and jitter parameters. Testing was conducted using Wireshark software during peak office hours in January and February 2023. The latency parameter findings were 3.49 ms in January and 4.89 ms in February on the main router (very good). The average jitter parameter was 3.49ms in January and 4.89ms in February (very good). The packet loss parameter is 2.05% (good) in February, while the overall average value in January is 0.83%. Overall, the calculation of the three parameters according to the TIPHON standardization is within a good range. His implementation of VRRP at the Sultan Iskandar Muda Weather Observatory proves the effectiveness of his VRRP in improving network availability and reliable backup systems.